Protection of consumer rights and interests - Kondrackaitė, Karolina; Kastanauskaitė, Ugnė (Vilnius University Open Series, 2020)
The object of this scientific article is protection of consumer rights and interests in contractual relationship between seller and consumer. The ever-expanding trade development, increasing abundance of goods and services stimulates consumption and this obviously leads to the growing number of consumer contracts. The growing number of consumer contracts determines the need to regulate contractual relations of consumers and sellers as much detail as possible. The purpose of detailed regulation is to prevent unfairness and ensure effective protection of the consumer as the weaker party. The work also draws attention to European Union law. The European Union law not only develops and ensures free movement of goods, services, capital and persons in a single market of European Union, but also seeks to discover a balance between the competitiveness of various companies in different Member States and a high level of consumer protection.
Keywords: none